Attacking science on social media: How user comments affect perceived trustworthiness and credibility - Gierth, Lukas (Public Underst Sci, 2019)
The science on controversial topics is often heatedly discussed on social media, a potential problem for social-media-based science communicators. Therefore, two exploratory studies were performed to investigate the effects of science-critical user comments attacking Facebook posts containing scientific claims. The claims were about one of four controversial topics (homeopathy, genetically modified organisms, refugee crime, and childhood vaccinations). The user comments attacked the claims based on the thematic complexity, the employed research methods, the expertise, or the motivations of the researchers. The results reveal that prior attitudes determine judgments about the user comments, the attacked claims, and the source of the claim. After controlling for attitude, people agree most with thematic complexity comments, but the comments differ in their effect on perceived claim credibility only when the comments are made by experts. In addition, comments attacking researchers’ motivations were more effective in lowering perceived integrity while scientists’ perceived expertise remained unaffected.